GANTI KERUGIAN TERHADAP ANAK KORBAN TINDAK PIDANA PENCABULAN - Murtadho, Achmad (Faculty of Law, Parahyangan Catholic University, 2021)
Children’s rights, as victim (of sexual offences) or perpetrator of crime, are not yet well secured or protected by law. This issue will be discussed by examining closely the substantive and procedural rules-regulation in the Law of Child Protection (no. 23 of 2002) and Law on Child Court (no. 11 of 2012). In addition, legal practice about children court shall also be highlighted. The author suggest that the prevailing substantive and procedural law has not yet be made adequately in response to the special needs of children victims of sexual abuse as well as accommodating the need for sufficient and fair compensation. It is as it is, due, amongst others, for the lack of victim perspective in the making of the children court system and how this system is being practiced.